2011
DOI: 10.1002/app.34891
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in percolation threshold of injection molded high‐density polyethylene/exfoliated graphene nanoplatelets composites by solid state ball milling and solid state shear pulverization

Abstract: Previous work showed that high density polyethylene (HDPE)/exfoliated graphene nanoplatelets (GNP) nanocomposites fabricated with melt extrusion followed by injection molding had a relatively high percolation threshold of between 10 and 15 vol % GNP loading. To lower the percolation threshold of injection molded HDPE/GNP nanocomposites, two special processing methods were investigated: solid state ball milling (SSBM) and solid state shear pulverization (SSSP). Results have confirmed that the percolation thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…The compounding method of fabricating PPS/GNP nanocomposites is solid state ball milling (SSBM) followed by compression molding. The reason of selecting this compounding method is because of its capability of achieving a high electrical conductivity in GNP nanocomposites as described in a previous study [25]. In the SSBM process, it was found that polymer particles are uniformly coated with GNP platelets which facilitate the formation of conductive pathways during the following injection molding or compression molding steps.…”
Section: Introductionmentioning
confidence: 96%
“…The compounding method of fabricating PPS/GNP nanocomposites is solid state ball milling (SSBM) followed by compression molding. The reason of selecting this compounding method is because of its capability of achieving a high electrical conductivity in GNP nanocomposites as described in a previous study [25]. In the SSBM process, it was found that polymer particles are uniformly coated with GNP platelets which facilitate the formation of conductive pathways during the following injection molding or compression molding steps.…”
Section: Introductionmentioning
confidence: 96%
“…A low molecular weight polyethylene sizing applied to the GnP greatly enhanced dispersion resulting in significant improvement in the HDPE/GnP electrical and mechanical properties. From the literature, it is reported that xGnP nanocomposites fabricated by solution casting tend to have lower percolation threshold or higher electrical conductivity than the samples made by melt-extrusion and injection molding [27]. The detailed study on the effect of xGnP on dielectric relaxation behaviour of the EVA has not been reported so far.…”
Section: Introductionmentioning
confidence: 96%
“…high mechanical strength and stiffness and high electrical and thermal conductivity) makes graphene one of the most promising candidates as nanofiller for fabrication of high strength and light weight polymer nanocomposites that can be used as conductive, antistatic, and electromagnetic interference shielding materials. [9,10] Over the past few years, graphene has been incorporated into a wide range of polymer matrices, which includes epoxy, [11] polyolefins, [12,13] polystyrene, [14] poly(methyl methacrylate), [15] polyesters, [16,17] polyamides, [18] and poly(vinyl alcohol), [19] for the development of various functional materials. It has been well reported in the literature that the incorporation of very small amount of graphene in polymer matrices led to a significant improvement in electrical and physical properties of polymer matrices.…”
Section: Introductionmentioning
confidence: 99%